THE - Fatima Tuzzahara Alkaf; Sri Widyastuti (Fakultas Pariwisata Universitas Pancasila, 2021)
The aim of this study was to analyze the increase in the tourism sector and to determine the position of the tourist destinations competitiveness in Nusa Tenggara Barat Province. This research methodology is a quantitative research and conducted technique analysis with Competitiveness Monitor (CM) Index, which is a method that can be used to measure the competitiveness of the tourism industry. The results of this study found that the competitiveness index of the Nusa Tenggara Barat (NTB) tourism industry in 2019 was higher than the results of the calculation of the competitiveness index in 2018. The competitiveness of the tourism sector in NTB Province continues to increase which is give benefit for PAD (Income Original Region) NTB Province. The finding of this study is expected to provide suggestions for local governments to be able to develop halal tourist destinations that are competitive and able to make the tourism sector one of the mainstays in contributing to Regional Original Income (PAD) which can improve community welfare.